PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING PADA ELEMEN ANALISIS DATA DAN PELUANG - Rahmi, Rahmi; Hamdunah, Hamdunah; Yunita, Alfi (Universitas PGRI Sumatera Barat, 2025)
The background of this research is because there are no electronic teaching materials that can help students to think critically, creatively and learn independently according to the demands of the independent curriculum in class X of SMA Negeri 1 Bungo and SMA Negeri 10 Tebo, Jambi Province. This study aims to produce valid and practical Electronic Student Worksheets (E-LKPD) based on Problem Based Learning on the element of data analysis and opportunity. This type of research is research and development using the ADDIE development model. The stages used in this development model are: analysis stage, design stage, development stage, implementation stage, and evaluation stage. The subjects of this study were class X students of SMA Negeri 1 Bungo and SMA Negeri 10 Tebo, Jambi Province. The research instruments used were observation sheets, interview guidelines, validity questionnaires and practicality questionnaires. Based on the results of the research and data analysis conducted, it can be concluded that the PBL-based E-LKPD on the element of data analysis and opportunity is in the very valid category with a percentage of 88.54%. The practicality of the use of PBL-based E-LKPD on the material of data analysis and opportunity element are 92.2% with a very practical category. The percentage results explain that the PBL-based E-LKPD on the element of Data Analysis and Opportunity are stated to be valid and practical.